Romania : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency for Romania. Romania has made progress in improving fiscal transparency. Over the last few years, the pace of reforms in this area and in strengthening the management of public finances has intensified, with the strong commitment to European Union accession serving as a catalyst. This has led to a significant amount of relevant legislation that has either been passed recently or is in the final approval stages.